Investigation of Relationship between Distortion Settlement, Lateral Spreading and Consolidation Settlement of a Selected Cohesive Soil - Valipourian, Komeil (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
Long-term settlement of foundation on clay soils is a well-known aspect of geotechnical design. Prediction of the performance of building foundations or embankments can be complicated and expensive in such ground conditions. Construction costs need to be balanced against high maintenance costs considering the long term performance. In order to do this optimally, there is a need to predict long term settlement with reasonable accuracy. For a reasonable prediction of long term settlement, it is crucial that ground investigation, laboratory testing and monitoring of ground settlement during and after construction are carried out. However, in most cases these are not possible to carry out in a project due to various reasons such as; increased construction costs, time and resource limitations etc. Hence, engineers commonly rely on punished empirical data on ground settlement behavior, which may sometimes be misleading. In order to reduce the cost of obtaining a reasonable prediction of long term settlement, it is proposed that the existence of a relationship between short term or immediate settlement and long term settlement is investigated. Immediate settlement of shallow foundations bearing on clay soils may constitute a significant part of the total settlement. Immediate settlement occurs due to the distortion of cohesive soils in untrained condition also defined as constant volume deformation. As part of this research, two basic mechanisms will be considered; 1- one dimensional consolidation settlement behavior (K=1 loading, in drained condition), and 2- one dimensional distortion settlement behavior (K= variable but controlled, in untrained condition). Two main goal were considered on the settlement behavior investigated using iv compacted specimens; the immediate settlement behavior and assessment of the relationship between the immediate settlement, consolidation settlement and the total settlement. For the Investigation of one dimensional distortion settlement behavior, a new testing equipment and testing methodology were designed. Experimental findings showed that as the confining stress increases, the immediate settlement indicates descending trend. It was concluded that the ratio of immediate settlement to long term settlement reduces as the value of confining stress increases. The results of this research are in good agreement with those in the literature on the ratio of immediate settlement to long term settlement. Keywords: consolidation settlement, cohesive soil, immediate settlement, lateral spreading

ÖZ: Geoteknik mühendisliği tasarımında temellerin killi zeminlerde uzun vadede gerçekleşen oturma davranışı iyi bilinen bir konudur. Böyler durumlarda bina veya dolgu temellerinin permormans tahminleri bazen oldukça zor ve masraflı olabilir. İnşaat bütçelerinin uzun vadedeki tamir masraflarını da düşünerek dengelenmesi gerekir. Bu iki unsuru optimize edebilmek için, uzun vadedeki davranışı hassas bir şekilde tahmin edebilmek gerekir. Uzun vadedeki davranışın hassas olarak tahmin edilebilmesi de zemin etüdü, laboratuvar analizleri ve arazide oturma takibi gerektirecektir. Birçok projede bunları gerçekleştirebilmek bazı sebeplerden dolayı mümkün olmayabilir; artan inşaat masrafları, zaman ve kaynak sıkıntıları bu sebeplerden sadece birkaçıdır. Bu nedenle, tasarım mühendisleri genellikle yayınlanmış deneysel veya tecrübeye dayalı verileri kullanmayı tercih ederler ki bunlardan bazıları tasarım hesaplarını yanlış yönlendirebilir. Uzun vadede gerçekleşen oturmanın daha hassas tespiti için kısa vadedeki oturmanın da iyi incelenmesi ve toplam oturma ile olan ilişkisinin araştırılması gerekmektedir. Kısa vadedeki oturma veya ani oturma, killi zeminlerde inşa edilen temellerin davranışının önemli bir kısmını teşkil edebilir. Ani oturma kohezyonlu zeminlerde drenajsız durumda ve sabit hacim koşulu ile şekil değiştirme (distortion) sonucunda meydana gelir. Bu tezdeki araştırma kapsamında, iki ana mekanizma düşünülmüştür; 1- bir boyutlu konsolidasyon oturma davranışı (K=1 yüklemesi, drenajlı durumda), ve 2- bir boyutlu şekil değiştirme sonucu oluşan oturma davranışı (K= değişken ancak kontrollü, drenajsız durumda). Bir boyutlu şekil değiştirme sonucu oluşan oturma davranışını incelemek için yeni deneysel metodoloji ve buna bağlı olarak vi ekipman oluşturulmuştur. Sıkıştırılmış numuneler üzerinde yapılan deneyler sonucunda oturma davranışı incelenmiş ve iki temel hedef belirlenmiştir; ani oturma davranışı ve ani oturma ile uzun vadede oturma davranışı arasındaki ilişkinin değerlendirilmesi. Deneysel çalışmalar göstermiştir ki, zemindeki çevresel efektif basınç yükseldikçe ani oturmada bir azalma elde edilmektedir. Ani oturmanın uzun vadedeki oturmaya oranı değerlendirildiğinde bu oranın çevresel efektif basınç artarken azaldığı bulunmuştur. Bu tezdeki deneysel sonuçların literatürdeki benzer diğer araştırmalar ile uygun sonuçlar verdiği gösterilmiştir. Anahtar kelimeler: ani oturma, kohezyonlu zemin, konsolidasyon oturması, yanal şekil değiştirme.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2016. Supervisor: Assist. Prof. Dr. Eriş Uygar.
Keywords: Civil Engineering; Soil Mechanics; Consolidation settlement; cohesive soil; immediate settlement; lateral spreading